Inventario de insectos asociados con arvenses en plantaciones de Gmelina arbórea Roxb. (melina) con control químico, mecánico y sin control, en los sectores La Palma del cantón Buena Fè, Yura Yacu, Lulo del cantón Valencia, y San Carlos del Cantón Quevedo de la Provincia de Los Ríos, año 2019. - Rosado Hernández, Delia Coralia (2019)
The present investigation was carried out in the sites of La Palma of Buena Fé Canton, Yura Yacu and Lulo of Valencia Canton and San Carlos of Quevedo Canton, province of Los Ríos, 2019. The general objective of the research was to determine the diversity of the insects are associated with the plantations of Gmelina arborea Roxb. (melina) with chemical, mechanical control and without control in the sectors already declared. The traps were installed in the center of the sampling units, one for each, that is, a total of three traps per site. The samples were collected in a container that contained 70% alcohol and 30% distilled water, the identification was carried out following the dichotomous keys. In total 48 species were collected with a total of 1,313 individuals with Lulo the site with the highest diversity with a value of 0.8546 according to Simpson and a value of 2,489 according to Shannon, the site with the lowest diversity in San Carlos with a Average diversity of 0.6167 according to Simpson and low diversity according to Shannon 1.306. The treatment with the greatest diversity was the mechanical treatment with 0.8726 (Simpson) and 2.518 (Shannon). The site with the highest abundance was San Carlos with 575 individuals and the lowest abundance was Lulo with 112 individuals, in the treatments; treatment 1 was the one that had the most individuals with 622 and the one with the lowest abundance was treatment 3 with 295 individuals. It was concluded that of the 48 related species; Epilachna tredecimnotat, Stigmene acrea, Atta cephalote, Pycnoscelus surinamensis, can be dangerous for planting and become pests. It was also determined that Podisus nigrispinus and Scolopendra polymorpha.son are biological controllers and may be favorable for the plantation Keywords: Diversity, insects, abundance, tramps, weeds, chemical control, mechanical control.